Case report: Double mutations in a patient with early-onset Alzheimer’s disease in China, PSEN2 and IDE variants - Chang, Zhongzheng; Wang, Zhiyang; Luo, Lele; Xie, Zhaohong; Yue, Caibin; Bian, Xianli; Yang, Hui; Wang, Ping (Frontiers in Neuroscience, 2024)
Alzheimer’s disease (AD) is a progressive neurodegenerative disease characterized by gradual cognitive decline. Early-onset Alzheimer’s disease (EOAD) is defined as AD occurring before age 65. The main pathogenic gene variants associated with EOAD include PSEN1, PSEN2, and APP. IDE gene has been identified as a risk factor in the pathogenesis of AD. In this study, we report a 33-year-old male with mutations in the PSEN2 gene (c.640G > T, p.V214L) and IDE gene (c.782G > A, p.R261Q). PSEN2 V214L has been reported in five previous cases, and no reported cases have carried IDE R261Q. He had progressive memory decline, his sister carried the same gene mutations but had no clinical manifestations. Neuroimaging revealed mild cortical atrophy. The concentration of Aβ42 in cerebrospinal fluid (CSF) was obviously decreased. In silico predictive models suggested that these mutations are damaging. Our findings indicate that mutations in the PSEN2 and IDE genes may disrupt the normal functioning of their respective proteins, contributing to the pathogenesis of AD.